Effects of Climate Change on the Distribution of Akebia quinata - Zhang, Jun-Ming; Song, Min-Li; Li, Zhen-Jian; Peng, Xiang-Yong; Su, Shang; Li, Bin; Xu, Xin-Qiao; Wang, Wei (Frontiers in Ecology and Evolution, 2021)
Akebia quinata, also known as chocolate vine, is a creeping woody vine, which is a Chinese herbal medicine, widely distributed in East Asia. At present, its wild resources are constantly destroyed. This paper aims to provide a theoretical basis for the resource protection of this plant species by analyzing the possible changes of its geographical distribution pattern and its response to climate factors. It is the first time to use MaxEnt and ArcGIS to predict the distribution of Akebia quinata in the past, the present and the future (four greenhouse gas emission scenarios of SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5). Through the prediction results, the impact of climate change on the distribution of Akebia quinata and the response of Akebia quinata to climate factors were analyzed. The results showed that the most significant climatic factor affecting the distribution pattern of Akebia quinata was the annual precipitation. At present, the suitable distribution regions of Akebia quinata are mainly distributed in temperate zone, and a few suitable distribution regions are in tropical zone. The medium and high suitable regions are mainly located in East Asia, accounting for 51.1% and 81.7% of the world's medium and high suitable regions respectively. The migration of the geometric center of the distribution regions of Akebia quinata in East Asia is mainly affected by the change of distribution regions in China, and the average migration rate of geometric center under each climate scenario is positively correlated with the level of greenhouse gas emission scenario.